Orbital magnetic moment and single-ion magnetic anisotropy of the S = 1/2 K3(Fe(CN)6) compound: a case where the orbital magnetic moment dominates the spin magnetic moment - Retegan, Marius; Jafri, Sadaf Fatima; Curti, Leonardo; Lisnard, Laurent; Otero, Edwige; Rivière, Eric; Haverkort, Maurits W.; Bleuzen, Anne; Sainctavit, Philippe; Arrio, Marie-Anne (Inorganic chemistry, 2023)
The potassium hexacyanoferrate(III), K3[FeIII(CN)6], is known for its exceptional magnetic anisotropy among the 3d transition metal series. The Fe(III) ions are in the S = 1/2 low spin state imposed by the strong crystal field of the cyanido ligands. A large orbital magnetic moment is expected from previous publications. In the present work, X-ray magnetic circular dichroism was recorded for a powder sample, allowing direct measurement of the Fe(III) orbital magnetic moment. A combination of molecular multiconfigurational ab initio and atomic ligand field multiplets calculations provides the spin and orbital magnetic moments for the [FeIII(CN)6]3− isolated cluster, the crystallographic unit cell, and the powder sample. The calculations of the angular dependencies of the spin and orbital magnetic moments with the external magnetic induction direction reveal easy magnetization axes for each S = 1/2 molecular entity and the crystal. It also shows that the orbital magnetic moment dominates the spin magnetic moment for all directions. Our measurements confirm that the orbital magnetic moment contributes to 60% of the total magnetization for the powder, which is in excellent agreement with our theoretical predictions. An orbital magnetic moment greater than the spin magnetic moment is exceptional for 3d transition metal ions. The impact of crystal field strength and distortion, π back-bonding, spin-orbit coupling, and external magnetic induction was analyzed, leading to a deeper understanding of the spin and orbital magnetic anisotropies.